Depression and Anxiety in Mothers Who Were Pregnant During the COVID-19 Outbreak in Northern Italy: The Role of Pandemic-Related Emotional Stress and Perceived Social Support - Grumi, Serena; Provenzi, Livio; Accorsi, Patrizia; Biasucci, Giacomo; Cavallini, Anna; Decembrino, Lidia; Falcone, Rossana; Fazzi, Elisa Maria; Gardella, Barbara; Giacchero, Roberta; Guerini, Paola; Grossi, Elena; et al. (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic is a collective trauma that is threatening citizens’ mental health resulting in increased emotional stress, reduced social support, and heightened risk for affective symptoms. The present study aimed to investigate the effects of antenatal pandemic-related emotional stress and perceived social support on the symptoms of depression and anxiety of mothers who were pregnant during the initial COVID-19 outbreak in northern Italy. A sample of 281 mothers was enrolled at eight maternity units in the first hotspot region of the COVID-19 outbreak in northern Italy. Participants filled out online questionnaires assessing the direct or indirect exposure to the SARS-CoV-2 virus, pandemic-related stress, perceived social support, as well as symptoms of depression and anxiety. Depressive and anxious symptomatology was above clinical concern respectively in 26% and 32% of the respondents. Mothers who reported no exposure to SARS-CoV-2 during pregnancy and those who reported at least one direct or indirect exposure did not differ in terms of affective symptoms. Continuous scores and risk for severe depression and anxiety were positively associated with prenatal pandemic-related emotional stress and negatively linked with perceived social support during pregnancy. Women who become mothers during the COVID-19 emergency may be at high risk for affective problems. Dedicated preventive programs are needed to provide adequate preventive support and care for maternal mental health during and after the COVID-19 pandemic.